The State of Violence or State Violence? Analysis of the Government’s Discourse about "Critical Neighborhoods" in Chile - Durán, Andrés; Abarca, Fariel; Álvarez, Francisco; Castro, Felipe; Hidalgo, Rodolfo (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
The present work makes a reading of the action of the State on the so-called "critical" neighborhoods, problematizing the perspective that has been built on "violence" that occurred in the sectors. It is argued that targeting “direct” violence, that is, interpersonal violence, and always located in politically delimited locations, is one of the forms that contemporary governmentality has acquired for the administration of life in the popular sectors. It is concluded that a socio-historical examination of the problem must consider the State, its speeches and writing as part of the problem to be analyzed, since it fully participates in its historical production as a rationality of government.
Keywords: Critical Neighborhoods; Governmentality; Writing; Violences